Impingement Flow Study on Temperature Profile of Concave Plate - Wong, Kok Yung (Universiti Sains Malaysia, 2021)
Anti-icing system is installed to prevent ice accretion on the body of aircraft. The system is important for aviation safety because ice accretion degrades the performance of the aircraft and may cause air crash. The impingement flow of hot air from Piccolo tube creates hotspot on nacelle lip skin and edges of wings. Improper heating may cause high thermal stress and damage the nacelle lip skin and edges of wings. Therefore, temperature distribution caused by the impingement of hot air must be studied for better design of anti-icing system. The impingement of hot air was simulated by using ANSYS Fluent 19.2. The temperature contour plots were obtained from the software. The validation was successfully done by using the correlation between Nusselt number on impingement point and Reynolds number. The dimensionless temperature of concave plate increases when Reynolds number increases and hot air temperature decreases. The highest dimensionless temperature recorded is 0.147125 under the set of 300mm curvature radius, air temperature of 43°C, Reynolds number of 4070. The dimensionless temperature of the plate decreases with the curvature radius decreases due to the increase of heat dissipation. The dimensionless temperature increases from 0.138747 to 0.142316 when the curvature radius increases from 150mm to 300mm.